Multiple pathways of the actin-myosin cycle in energy transduction and the release of orthophosphate in muscle - Caremani, Marco; Pertici, Irene; Morotti, Ilaria; Bianco, Pasquale; Reconditi, Massimo; Piazzesi, Gabriella; Lombardi, Vincenzo; Linari, Marco (Frontiers in Physiology, 2025)
In the striated muscle, the molecular motor myosin II functions in two bipolar arrays in each thick filament, converting chemical energy into steady force and shortening by cyclic ATP-driven interactions with nearby actin filaments. The fundamental steps in energy transduction are the working stroke, an inter-domain tilting of the lever arm about the actin-attached catalytic domain, generating up to ∼5 pN force or ∼10 nm of filament sliding, and the release of the ATP hydrolysis product orthophosphate (Pi) from the nucleotide-binding site, which is associated with a large free energy release. The two events are not simultaneous, as first demonstrated by the force response to a stepwise change in [Pi] (the Pi transient), showing the saturation kinetics characteristic of a two-step reaction. However, while high-resolution crystal structures of the myosin motor suggest that Pi release precedes the working stroke, in vitro functional studies indicate that it follows the working stroke. High-resolution sarcomere-level mechanics applied to single muscle fibers, allowing myosin motor synchronization by step perturbations in length or load, revealed that the kinetics of the working stroke is independent of [Pi] and depends only on the load. Moreover, this approach highlights the need for two unconventional pathways of the chemo-mechanical cycle: an early detachment of the force-generating motors and the possibility for attached motors to slip to the next actin monomer farther from the sarcomere center during shortening. Transient and steady-state responses to stepwise changes in load or [Pi] can be fitted with a structurally and biochemically explicit model in which the Pi release step is orthogonal to the progression of the working stroke. Model simulations indicate that the rate of Pi release depends on motor conformation, which resolves longstanding unanswered questions such as the dependence of Pi transient kinetics on the final level of [Pi] under any load and clarifies the issue of the relative timing between the working stroke and Pi release: at high loads, Pi release precedes the execution of the working stroke, while at low loads, the working stroke state transitions are fast enough to occur with Pi still bound to the catalytic site.